(untitled) (Archive of Conferences, 2020)
Today, the use of world experience in teaching science is a requirement of the time. In this regard, it is important to prepare for international research, to establish science teaching based on the integration of disciplines. This article focuses on the importance of interdisciplinary integration in the primary education system.